A Quantitative Model for Alkane Nucleophilicity Based on C−H Bond Structural/Topological Descriptors. (21st January 2020) - Besora, Maria; Olmos, Andrea; Gava, Riccardo; Noverges, Bárbara; Asensio, Gregorio; Caballero, Ana; Maseras, Feliu; Pérez, Pedro J.
Abstract: A first quantitative model for calculating the nucleophilicity of alkanes is described. A statistical treatment was applied to the analysis of the reactivity of 29 different alkane C−H bonds towards in situ generated metal carbene electrophiles. The correlation of the recently reported experimental reactivity with two different sets of descriptors comprising a total of 86 parameters was studied, resulting in the quantitative descriptor‐based alkane nucleophilicity (QDEAN) model. This model consists of an equation with only six structural/topological descriptors, and reproduces the relative reactivity of the alkane C−H bonds. This reactivity can be calculated from parameters emerging from the schematic drawing of the alkane and a simple set of sums. Abstract : Das QDEAN‐Modell stellt einen ersten Ansatz zur quantitativen Modellierung der Reaktivität von Alkan‐C‐H‐Bindungen gegenüber Elektrophilen dar. Eine bemerkenswerte Korrelation zwischen experimentellen und berechneten Werten wurde mit nur sechs topologischen Deskriptoren für die untersuchten C‐H‐Bindungen erreicht.